Direct Electrochemical Determination of Glyphosate Herbicide Using a Screen-Printed Carbon Electrode Modified with Carbon Black and Niobium Nanoparticles - Fernandes, Julia Oliveira; Bernardino, Cassiano Augusto Rolim; dos Santos Fernandes, Juliana; Mahler, Claudio Fernando; Braz, Bernardo Ferreira; dos Santos, Luiz Henrique Carpenter; Corrêa, Rodrigo José; Santelli, Ricardo Erthal; Archanjo, Braulio Soares; Ribeiro, Emerson Schwingel [UNESP]; Cincotto, Fernando Henrique (Springer Nature, 2023)
Glyphosate is a herbicide that has been widely used worldwide and is used in agricultural areas to control weeds and unwanted vegetation. Electrochemical sensors developed from different nanomaterials have high efficiency, excellent cost–benefit, and fast analysis time for detecting traces of environmental pollutants. This study aimed to produce an electrochemical sensor with disposable screen-printed electrodes based on carbon black modified with niobium nanoparticles to determine glyphosate in aqueous solutions. The morphology, structure and electrochemical performance of the sensor were characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction and cyclic voltammetry. Differential pulse voltammetry in BR buffer solution at pH 5.0 allowed the generation of a method to quantify glyphosate concentration in a linear range of 5.90–172.30 µmol/L (1.00–29.13 µg/mL), with a limit of detection calculated at 3.07 µmol/L (0.52 µg/mL). The method efficiently quantified glyphosate in real water samples and showed no interference from K+, Na+, Ca2+, Mg2+ ions or thiamethoxam, imidacloprid and carbendazim pesticides.
Keywords: Carbon black; Electrochemical sensor; Glyphosate; Niobium nanoparticles